Acute and Chronic Pheochromocytoma-Induced Cardiomyopathies: Different Prognoses?. Issue 50 (December 2015) - Batisse-Lignier, Marie; Pereira, Bruno; Motreff, Pascal; Pierrard, Romain; Burnot, Christelle; Vorilhon, Charles; Maqdasy, Salwan; Roche, Béatrice; Desbiez, Francoise; Clerfond, Guillaume; Citron, Bernard; Lusson, Jean-René; et al.
Abstract : Abstract: Pheochromocytoma and paraganglioma (PPG) are rare and late-diagnosed catecholamine secreting tumors, which may be associated with unrecognized and/or severe cardiomyopathies. We performed a computer-assisted systematic search of the electronic Medline databases using the MESH terms "myocarditis, " "myocardial infarction, " "Takotsubo, " "stress cardiomyopathy, " "cardiogenic shock", or "dilated cardiomyopathy, " and "pheochromocytoma" or "paraganglioma" from 1961 to August 2012. All detailed case reports of cardiomyopathy due to a PPG, without coronary stenosis, and revealed by acute symptoms were included and analyzed. A total of 145 cases reports were collected (49 Takotsubo Cardiomyopathies [TTC] and 96 other Catecholamine Cardiomyopathies [CC]). At initial presentation, prevalence of high blood pressure (87.7%), chest pain (49.0%), headaches (47.6%), palpitations (46.9%), sweating (39.3%), and shock (51.0%) were comparable between CC and TTC. Acute pulmonary edema (58.3% vs 38.8%, P = 0.03) was more frequent in CC. There was no difference in proportion of patients with severe left ventricular systolic dysfunction (LV Ejection Fraction [LVEF] < 30%) at initial presentation between both groups ( P = 0.15). LVEF recovery before (64.9% vs 40.8%, P = 0.005) and after surgical resection (97.7% vs73.3%, P = 0.001) was higher in the TTC group. Death occurred in 11 cases (7.6%). In multivariate analysis, only TTC was associated with a better LV recovery (0.15 [0.03–0.67], P = 0.03). Pheochromocytoma and paraganglioma can lead to different cardiomyopathies with the same brutal and life-threatening initial clinical presentation but with a different recovery rate. Diagnosis of unexplained dilated cardiomyopathy or TTC should lead clinicians to a specific search for PPG.